(untitled) (Journal of Buffalo Science, 2024)
The study was divided into 2 phases. During 1st phase, 20 pre-partum buffaloes were divided into two groups, given -100 (high negative; HN) and -50 (low negative; LN) mEq/kg of dry matter (DM) diets. In the second phase, +200 (low positive; LP) and +400 (high positive; HP) mEq/kg of DM diets were formulated for postpartum buffaloes. Buffaloes that received LN DCAD were divided into 2 groups (LN-LP and LN-HP), and those that received HN DCAD were also divided into 2 groups (HN-LP and HN-HP). In the first phase, the group fed the HN DCAD diet had significantly lesser DM, nutrient intake, and urine pH (p<0.05) but higher ME intake and ADF digestibility. Also, higher serum phosphorus levels (p<0.05), fewer cases of hypocalcemia and ketosis, and a relatively smaller decrease in body weight were reported with the HN group. In the second phase, DM, organic matter, and NDF intakes were higher (p<0.05) in HN-HP and LN-LP groups, whereas ME intake and nutrient digestibility were higher in HN-LP and LN-HP (p<0.05). Daily milk, solid not fat (SNF), fat, protein, lactose yields, and plasma total protein, urea, and cholesterol concentrations were the highest in the HN-HP group (p<0.05), but the highest fat content and fat yield were recorded in the HN-LP group (p<0.05). Better efficiency of milk production and the lowest cases of hypocalcemia and ketosis were observed for both groups. In conclusion, for transition buffaloes, the HN and LN DCAD (-100 and +200 mEq/kg of DM, respectively) diets showed a beneficial impact.